PERLINDUNGAN HUKUM TERHADAP BURUH WANITA YANG BEKERJA DI LUAR NEGERI DALAM PERSPEKTIF HUKUM INTERNASIONAL (Lex Jurnalica, 2021)
One of the country's foreign exchange earnings is from the Indonesian Labor sector, in this case they work as laborers abroad. Female workers who come from Indonesia who work abroad usually become domestic helpers, mill hand  and other abusive sectors. However, the nickname ‘pahlawan devisa’  does not guarantee that Indonesian workers are treated like heroes. There are still many polemics faced by migrant workers abroad, such as being treated unfairly and arbitrarily by their employers, to the death penalty cases for migrant workers abroad. Using a normative legal approach, and through literature studies, the Republic of Indonesia is committed to providing legal protection for its people even though they are in trouble abroad through applicable international law.